Možnosti studia evangelické sakrální architektury - Altová, Blanka (Lidé města, 2009)
The article examines the possibilities of studying Protestant sacral architecture constructed in the Czech lands from the era of the issuing of the Edict of Tolerance in 1781 to the present. The registers of individual church congregations were used as the foundation for a basic art history study, as a collection of historical image sources in the ecclesiastical, cultural and social context. The aim was not to create an abstract collection of the development in the fine arts, but to analyse the form and content, deciphering the intentions of the builders and constructors. Architecture as a work of art gives witness to ambitions, visions – to what could or should be, and also to the real possibilities and situations of the constructors. It is a part of visual communication, inside the church itself, as well as in the wider social framework of state, nation and location. Protestant sacral architecture captured echoes of the “national” styles and the roots of the modern Czech Protestant tradition. The findings were compared with generally accepted meanings of the used symbols (or their systems, e.g. styles, construction typologies) in the given period and cultural space as was written in contemporary texts or that are somehow interpreted in current academic literature. At the same time, the specifics of the Protestant perception of the sacred are noticed, as is the influence of theology and liturgy on the organisation of the construction. The set of Protestant sacral constructions was divided chronologically according to significant historical moments in political history; the study examined to what extent did the history of the given churches intermingle with the history of political and social developments. It is shown that historical events and turning points have an indirect influence on Protestant sacral architecture; chiefly, they touch and effect people and their relations to church.